Bycatch-neutral fisheries through a sequential mitigation hierarchy. (April 2023) - Gilman, Eric; Chaloupka, Milani; Booth, Hollie; Hall, Martin; Murua, Hilario; Wilson, Jono
Abstract: Fisheries bycatch is the foremost threat to the conservation of many marine species. Evaluation of alternative bycatch management strategies can account for the relative strength of evidence, contribution to achieving objectives, costs to commercial viability, likelihood of compliance and tradeoffs from multispecies conflicts. This study describes benefits and limitations of a complementary approach of applying a sequential mitigation hierarchy to develop evidence-informed bycatch policy. Measures that avoid bycatch are considered before those that minimize catch risk. These are then followed by remediation interventions that reduce fishing mortality and sublethal impacts. Finally, direct, compensatory banking or in lieu fee-based offsets of residual impacts that were not possible to avoid, minimize and remediate can be implemented as a last resort. However, offset activities can be socioeconomically unjust, and some bycatch impacts are irreversible and cannot be offset. Air-breathing bycatch are exposed to a wide range of anthropogenic hazards across ontogenetic stages, presenting more options for offset conservation activities than fishes. Averted loss offsets, which avoid foregone losses predicted to occur had an intervention not occurred, implemented in combination with true offsets can achieve at least an equivalent gain and contribute to meeting broad, population- and species-level conservation objectives. Robust metrics are needed to determine equivalency, such as in relative reproductive value and population viability, between residual impacts and in-kind versus out-of-kind and on-site versus offsite offsets. Bycatch management strategies guided by a sequential mitigation hierarchy promise to achieve ecological and socioeconomic objectives, including going bycatch-neutral or bycatch-negative through a net biodiversity gain. Highlights: Fisheries bycatch is the leading threat to many marine species. Evidence-informed bycatch policy should apply a sequential mitigation hierarchy. Identifies benefits and risks of a mitigation hierarchy for bycatch management. Direct and compensatory offsets can obtain equivalent gains for bycatch losses. Robust metrics are needed to determine equivalency.